My Dad is brilliant - Butterworth, Nick (Walker Books Ltd London, 2016)
This Dad is, quite simply, brilliant! He's as strong as a gorilla, fantastic on roller skates, and can sing like a pop star! Find out what else he can do in this colourful book that bursts with appreciation for Dads